Develops The Software of DSP Processor for the CDMA circuitry - D., Arman Djohan (Makara Journal of Technology, 2002)
This research develops the software of DSP Processor type TMS320C54X for the CDMA circuitry. This research apply two algorithms namely Mathematic Algorithm and table lookup Algorithm. From both algorithms, the research examine what algorithm have the fasted processing time and the smallest memory occupation. From the examination results the Mathematic Algorithm have 20.62 milliseconds processing time and the Table lookup algorithm have 14.08 milliseconds processing time. The Table lookup algorithm have the fastest processing time because the Matematic algorithm need the rounding process of the fi gure. Eventhough such processing time is not exceed from the 125 millisecond of delay time, in real condition, the total processing time are include the error correction processing time and voice compression processing time such as ADPCM or QCELP voice compression techniques.